Fluorodeoxyglucose positron emission tomography for detection of tumor recurrence following radiofrequency ablation in retrospective cohort of stage I lung cancer. (31st December 2018) - Wang, Yingbing; Lanuti, Michael; Bernheim, Adam; Shepard, Jo-Anne O.; Sharma, Amita
Abstract: Purpose: The goal of this study was to define patterns for tumor recurrence on PET following RFA, compare time to imaging recurrence by PET versus CT, evaluate whether pre-treatment tumor uptake predicts recurrence and propose an optimal post-RFA surveillance strategy. Materials and methods: A retrospective cohort study was performed of biopsy confirmed primary stage I lung cancers treated with RFA. FDG PET and near contemporaneous diagnostic CT imaging pre-ablation, within 30 days post-ablation, and beyond 6 months were independently and retrospectively evaluated for features supportive of recurrence. Time to imaging recurrence by PET (TTR_PET) and by CT (TTR_CT) were determined and compared. FDG avidity of untreated tumors was compared between recurrent and non-recurrent groups. Results: Thirteen recurrences after 72 RFA treatments were confirmed by diagnostic CT. All recurrences were associated with focally intense and increasing FDG uptake beyond 6 months (sensitivity 100%; specificity 98.5%). Mean TTR_PET was 14 months compared to mean TTR_CT of 17 months (not statistically significant). Normalized SUVmax and total lesions glycolysis of lung cancers that recurred after RFA was 4.0 and 6.0, respectively compared to 2.8 and 5.0, respectively for cancers that did not recur ( p  = .068). Conclusion: A pattern of focally intense and increasing FDG PET uptake has high sensitivity and specificity for detecting recurrent lung cancer following RFA. Surveillance after RFA should include a contrast enhanced diagnostic CT at 1 month to diagnose procedural complications, PET at 6 months as a post-treatment metabolic baseline (with diagnostic CT if PET is abnormal) and alternating diagnostic CTs or PET every 6 months for 2 years.